ASBESTOS IN NATURAL AND ANTHROPIC OPHIOLITIC ENVIRONMENTS: A CASE STUDY OF GEOHAZARDS RELATED TO THE NORTHERN APENNINE OPHIOLITES (EASTERN LIGURIA, ITALY) - Gaggero, Laura; Crispini, Laura; Isola, Evelina; Marescotti, Pietro (Ofioliti, 2013)
Asbestos-related environmental issues include: i) the presence of natural outcrops of asbestos-bearing rocks, ii) the cycle of asbestos within natural matrix- es, and iii) the quantitative assessment of asbestos fibres within large volumes of rock. The characterisation of the origin of asbestos as an exogenous agent, or during anthropogenic activity and the subsequent dispersal of fibres in neighbouring areas, allows the definition of a “fibre-cycle”, which is overall parallel to the hydric cycle. Pilot studies using microstructural and mineralogical investigations to assess the distribution and approximate volumes of asbestos minerals and their potential contribution of airborne fibres were undertaken at six quarry sites within the very-low-grade metamorphic ophiolites of the Northern Apen- nines in eastern Liguria, Italy. These studies also incorporated the assessment of the abundance of fibres within heaps of sedimentary debris within the same quarries; this assessment focused on heaps that were formed during natural erosion in addition to those formed during mineral extraction. This study also tested a protocol that aimed to improve the Italian DM 16/5/1994 Release Index by addressing the issue of multi-scale analyses that are tai- lored for studies from outcrop scales to the microscale by integrating multiple techniques (optical microscopy, scanning electron microscopy, XR diffractome- try, µ-Raman, geomechanical analysis, and modal petrographic analyses).